A Chinese cohort study on Henoch-Schönlein purpura nephritis: Design and methods. (31st May 2018) - Zou, Xin-Rong; Xue, Xue; Wang, Chang-Jiang; Han, Si-Ping; Chen, Hong; Yuan, Jun; Wang, Xiao-Qin
Henoch-Schönlein purpura (HSP) is a kind of allergic systemic necrotizing vasculitis. The incidence of renal involvement is 30%–50% in HSP patients. A recent national survey demonstrated that the treatment results of several randomized controlled trial (RCT) studies on Henoch-Schönlein purpura nephritis (HSPN) using Western medicine, such as glucocorticoids, immunosuppressive agents, and supportive therapy, were not satisfactory. Hence, there is a need to explore traditional Chinese medicine (TCM) syndrome elements and its related factors of HSPN in the real world to observe the clinical curative effect of TCM treatment. The Chinese Cohort Study of HSPN is the first national HSPN cohort in China. This study will enroll approximately 350 HSPN patients who are within 14–74 years old and will be followed up for 24 months. Questionnaires, body measurement, laboratory tests, and biomaterials will be collected at baseline, quarterly, and annually. The principal clinical outcomes of the study will include the summing up of TCM syndrome elements and its related factors of HSPN. At the same time, the clinical effect of TCM in alleviating the clinical uncomfortable symptoms of HSPN, proteinuria, and renal function will be observed and confirmed. This study will provide important evidences for the constitution and clinical effect of TCM syndrome elements and lay a foundation for further conducting RCT clinical research on the treatment of HSPN by TCM. At the same time, this will provide valuable information to establish clinical guidelines and healthcare policies for TCM treatment of HSPN in China.